Ultrahigh electrically and thermally conductive self-aligned graphene/polymer composites using large-area reduced graphene oxides - Kumar, Pradip; Yu, Seunggun; Shahzad, Faisal; Hong, Soon Man; Kim, Yoon-Hyun; Koo, Chong Min (PERGAMON-ELSEVIER SCIENCE LTD, 2016)
In this work, for the first time we fabricated highly self-aligned large-area reduced graphene oxide/poly (vinylidene fluoride-co-hexafluoropropylene) (rLGO/PVDF-HFP) composite films through simple solution casting followed by low temperature chemical reduction process. The resulting free-standing rLGO/PVDF-HFP composite thin film revealed excellent electrical conductivity of similar to 3000 S/m and ultrahigh inplane thermal conductivity of similar to 19.5 W/mK at rLGO content of 27.2 wt %. This ultrahigh electrical and thermal conductivity were attributed to the good interfacial interaction, effective chemical reduction, high aspect ratio, and preferential orientation of graphene sheets along the film direction. We believe that our new fabrication procedure can be effectively used for large-scale production and commercialization of conductive composite materials for many thermal and electrical conduction applications. (C) 2016 Elsevier Ltd. All rights reserved.
Keywords: IN-SITU REDUCTION; POLYMER COMPOSITES; INTERFACE MATERIALS; FACILE ROUTE; NANOCOMPOSITES; ALIGNMENT; HYBRIDS; FILMS; SIZE